2013
DOI: 10.1111/1471-0528.12150
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the challenge of interpreting high‐resolution single nucleotide polymorphism array data in prenatal diagnosis: does increased diagnostic power outweigh the dilemma of rare variants?

Abstract: Objective Several studies have already shown the superiority of chromosomal microarray analysis (CMA) compared with conventional karyotyping for prenatal investigation of fetal ultrasound abnormality. This study used very high‐resolution single nucleotide polymorphism (SNP) arrays to determine the impact on detection rates of all clinical categories of copy number variations (CNVs), and address the issue of interpreting and communicating findings of uncertain or unknown clinical significance, which are to be e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 37 publications
(49 reference statements)
1
50
2
Order By: Relevance
“…CMA analyses enable focusing on gene alterations that are below the detectable levels of known genetic abnormalities [Kearney et al, 2011;Ganesamoorthy et al, 2013]. CMA analysis in the current study revealed heterogenic genetic changes.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…CMA analyses enable focusing on gene alterations that are below the detectable levels of known genetic abnormalities [Kearney et al, 2011;Ganesamoorthy et al, 2013]. CMA analysis in the current study revealed heterogenic genetic changes.…”
Section: Discussionmentioning
confidence: 67%
“…Advances in microarray technology allow high-resolution, genome-wide evaluation of DNA copy number variations (CNVs) -both deletions and duplicationsand opens new directions for research connecting genetics to abnormal placentation [Founds et al, 2009;Ganesamoorthy et al, 2013;Madeleneau et al, 2015;Rabaglino et al, 2015]. It is a significant tool for identifying genomic alterations leading to diseases.…”
mentioning
confidence: 99%
“…Indeed, we also observed CNV's representing known and well-documented polymorphisms or inherited benign/low risk variants for which counseling is relatively straightforward, while in our series we did not come across any (un-interpretable) variants of unknown clinical significance. This is in contrast, however, with the multitude of VOUS detected by higher resolution aCGH platforms, with figures ranging from 1-4% [48,50,51], necessitating parental follow-up studies and complicated genetic counseling and perhaps these drawbacks cannot be offset by the slightly higher detection rate.…”
Section: Resultsmentioning
confidence: 99%
“…A positive correlation between array resolution and the detection rate of pathogenic CNVs as well as of VOUS is likely and not unexpected [39,40]. Srebniak et al [41] have demonstrated this by retrospectively reassessing high resolution genome-wide array data of 456 fetuses at different resolution levels.…”
Section: Resultsmentioning
confidence: 99%